Knowledge infrastructure development as panacea to quality assurance in higher education in Nigeria (2019)
Knowledge is a pre-requisite to any significant level of infrastructure development. The paper emphasized knowledge infrastructure development as panacea to quality assurance in higher education in Nigeria. From preliminary observation, there may not be meaningful, Creative and deepened use of technology for teaching, learning and research activities in higher institutions without the availability and adequacy of knowledge infrastructure. The methodology adopted for this paper was literature-based approach. The literature consulted covered the period of 1995 to 2017. The materials consulted for the literature survey include scholarly journals, textbooks, conference proceedings, and Internet sources. Contextual information from the information materials were studied comparatively, discussed and inferences were drawn from the literature. The concept of knowledge infrastructure has been discussed in the paper to reflect new knowledge practices captured under the language of crowd sourcing, cyber-infrastructure, personal informatics, citizen science, open access, among others. The paper further discussed the process of knowledge infrastructure which centred on knowledge accumulation, integration, and reconfiguration. In addition, knowledge infrastructure as panacea to quality assurance in higher education reflects quality use of information by access control. The paper concludes that investment in knowledge infrastructure would make African countries to compete with the rest of the global world in terms of infrastructural development. The recommendations therefore include provision of relevant ICT tools to aid library services; improvement of library personnel ICT skills; and readiness to use knowledge infrastructure by library users.